อิทธิพลของเสาเข็มเอียงต่อความลึกหลุมกัดเซาะของเสาเข็มกลุ่ม - พีระ ฉัตรจินตนาพร (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This experimental study aims at the investigation of the effects of the inclination of the front pile of pile groups on the maximum scour depth around group piles. Four different pile inclination angles of 5°, 10°, 15° and 20° in the combination of three different horizontal inclination planes, consisting of the planes parallel to, diagonal to, and perpendicular to the flow direction, respectively were tested. In the study, uniform sediment with the mean particle size of 0.27 mm was used as channel bed material. The experiments were carried out under steady and subcritical flow, and under clear-water scour conditions. A 2-pile group arranged in tandem and a 3-pile group arranged in a right-angle triangle with the side-by-side and tandem pile spacing 2-times pile diameter were used. The experiment results showed the significant pile inclination effects on the pile scour depth. It has been found that the maximum scour depth decreased as the inclined angle increased for the plane parallel to the flow. For the inclination plane perpendicular to the flow direction, the maximum scour depth tended to increase as the inclined angle increased. However, for the inclination plane diagonal to the flow direction the maximum scour depth was apparently unchanged, comparing to the scour depth of the vertical pile group. Additionally, the experiment result presents an equation for determining the effective diameter to predict the maximum scour depth of the inclined pile. The presented equation describes the observation data fairly good.